System-level responses to cisplatin in pro-apoptotic stages of breast cancer MCF-7 cell line. (December 2019) - Fallahi, Hossein; Godini, Rasoul
Graphical abstract: Highlights: Cisplatin induces subtle differences between two pro-apoptotic stages in the MCF-7 cell line. Cisplatin affect several major processes including transcription, ubiquitination etc. at early stages. While at the later stages of cisplatin treatment, the metabolite contents of the cells will be affected. Abstract: Cisplatin ceases cell division and induces apoptosis in cancer cell lines. It is well established that cisplatin alters the expression of many genes involved in several cellular processes and pathways including transcription, p53 signaling pathway, and apoptosis. However, system-wide responses to cisplatin in breast cancer cell lines have not been studied. Therefore, we have used a network analysis approach to unveil such responses at early stages of drug treatment. To do this, we have first identified those genes that are responding to cisplatin treatment in MCF-7 cell line. Network and gene ontology analyses were then employed to uncover the molecular pathways affected by cisplatin treatment. Then the results obtained from cisplatin-treated MCF7 cell line were compared to those obtained from other cancer cell lines at comparable time points. In conclusion, we found that ADCY9, GSK3B, MAPK14, NCK1, NCOA2, PIK3CA, PIK3CB, PTK2, RHOB act as hub genes in the cisplatin-responsive regulatory network at the pro-apoptotic stages. The results could be useful in finding new drugs to target these genes in order to obtain similar responses.